How to improve employee satisfaction and efficiency through different enterprise social media use. Issue 3 (15th July 2020) - Liang, Ma; Xin, Zhang; Yan, Ding Xiao; Jianxiang, Fei
Abstract : Purpose: While prior research provides interesting insights into the effect of social media use in enterprises, there is limited research on how use of different social media platforms affects employee job satisfaction and work efficiency. This study developed a research model to investigate how public and private social media platforms used for different motivations affect employee job satisfaction and work efficiency. Design/methodology/approach: Online surveys were conducted in China, generating 453 valid responses for analysis. Structural equation modeling is performed to test the research model and hypotheses. Findings: The results suggest that (1) public social media used for both work- and social-related motivations positively affects employee job satisfaction, while private social media only used for social-related motivations can contribute to employee job satisfaction. (2) Public and private social media used for work-related motivations can contribute to employee work efficiency, while social-related motivations for use of public and private social media and employee work efficiency are not significant. (3) In the process of social media usage influencing employee job satisfaction and work efficiency, employees of different genders show significant differences. Originality/value: First, this paper contributes to information systems social media research by examining the joint effects of different motivations for public and private social media usage on employee job satisfaction and work efficiency in organizations. Second, it contributes to uses and gratification theory by clarifying the relationship between different motivations for enterprise social media use and its needs.